ANALISIS USAHATANI KOMPARASI PADI SAWAH ANTARA VARIETAS UNGGUL DENGAN VARIETAS LOKAL - Idin, Idin; Dinar, Dinar; Ayu Andayani, Sri (Journal of Sustainable Agribusiness, 2025)
This study aims to determine the comparison of average cost productivity, income productivity, and farming profits with local varieties in the Pancakerta Farmer Group. This study was conducted from January 2025 to March 2025 in the Pancakerta Farmer Group. The method in this study used a survey method. The research design used a descriptive survey approach and farming analysis. A total of 30 respondents were determined using the Slovin method. The results of the analysis showed that the average productivity of superior varieties was 7.55 tons/ha/MT. While in local rice farming it was 8.98 tons/ha/MT. During one period and the average total cost incurred for each respondent of superior variety farming was IDR 34.792.399. while for local variety farming it was IDR 38.581.742. The income received from superior variety farming with 15 respondents was IDR 796.950.000 with an average of IDR 53.130.000/MT. Meanwhile, for local variety farmers, it is IDR 1.097.754,000 with an average of IDR 73.183.600. The average profit obtained from the superior variety farming business 32 is IDR 22.446.797 / MT while local varieties are IDR 34.840.670. The efficiency of superior variety farming with an average R / C value of 1.52 / MT, while local varieties are 1.90 / MT. This shows that farming of superior varieties and local varieties in the Pancakerta Group is efficient to be cultivated.